Political and Cultural Dynamics in Bollywood and Nollywood Films: A Comparative Perspective - Endong Floribert Patrick C.; Princess Emike Umole (International Journal of Media and Communication Research, 2024)
Films are popularly believed to be reflection of reality as well as a representation of the societies in which they were produced. They are excellent windows into their societies of origin and could thus serve as good anthropological or historical documents containing data about socio-political events that have happened in their societies of origin. One of the multiple data one can extract/gather from films is the socio-cultural and political dynamics prevailing in the society in which the films subsist. This paper attempts to illustrate this thesis through a review of relevant Bollywood and Nollywood films. Specifically, the study hinges on a review of relevant selected films to show how Bollywood and Nollywood are a reflection of cultural and political dynamics in India and Nigeria respectively. The paper starts with a brief background which examines the extent to which Nollywood and Bollywood films could be considered a reflection of contemporary Nigeria and India. It proceeds to defining the concept of cultural and political dynamics, with strict respect to the Indian and Nigerian experiences. The paper ends up with an examination of how these cultural and political dynamics are reflected in relevant Bollywood and Nollywood films. It concludes that both Nigerian and Bollywood films reflect social and political dynamics in their societies of origin in the same way.